The Effect of Capital Structure on Firm Value with Corporate Social Responsibility as a Moderating Variables - Wardani, Dewi Kusuma; Sulaeman, Icha (Proceedings International Conference on Education Innovation and Social Science, 2023)
This study aims to determine the effect of capital structure on firm value, with corporate social responsibility as a moderating variable. The population of this study is made up of manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2018–2021. The type of data used is secondary data taken from www.idx.co.id. Company value is proxied by Tobins' Q.The results of this study indicate that capital structure has a positive effect on firm value, and corporate social responsibility cannot moderate the positive effect of capital structure on firm value.